2015
DOI: 10.1186/s13326-015-0029-x
|View full text |Cite
|
Sign up to set email alerts
|

A framework for ontology-based question answering with application to parasite immunology

Abstract: BackgroundLarge quantities of biomedical data are being produced at a rapid pace for a variety of organisms. With ontologies proliferating, data is increasingly being stored using the RDF data model and queried using RDF based querying languages. While existing systems facilitate the querying in various ways, the scientist must map the question in his or her mind to the interface used by the systems. The field of natural language processing has long investigated the challenges of designing natural language bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 73 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Because the focus of their research is in transforming semantic structures identified in unstructured data sources (documents) to an RDF store that is accessible via natural language questions, the mapping of ontological concepts to (external) data sources is beyond the scope of their proposed framework. The same constraint holds true for OntoNLQA (Asiaee et al 2015), which was introduced to query RDF data annotated using ontologies to allow posing questions in natural language. In the clinical and clinical research contexts, Mate et al (2015) introduced a system for linking information of different systems using declarative transformation rules for ontologies of the source system and the target system.…”
Section: Ontology-based Applicationsmentioning
confidence: 98%
“…Because the focus of their research is in transforming semantic structures identified in unstructured data sources (documents) to an RDF store that is accessible via natural language questions, the mapping of ontological concepts to (external) data sources is beyond the scope of their proposed framework. The same constraint holds true for OntoNLQA (Asiaee et al 2015), which was introduced to query RDF data annotated using ontologies to allow posing questions in natural language. In the clinical and clinical research contexts, Mate et al (2015) introduced a system for linking information of different systems using declarative transformation rules for ontologies of the source system and the target system.…”
Section: Ontology-based Applicationsmentioning
confidence: 98%
“…Entity linking BERT transformer (60). Distant supervision (7). Joint entity and relation linking (41)…”
Section: Answering Complex Questionsmentioning
confidence: 99%
“…Asiaee et al. applied a KBQA solution to parasite immunology [7], and Hamon et al. created a querying platform for linked biomedical data [8].…”
Section: Introductionmentioning
confidence: 99%
“…Towards this goal, we leverage the Open Research Knowledge Graph 3 (ORKG) [20] and present a GraphQL-based endpoint 4 to access its data i.e., machine actionable descriptions of scholarly knowledge and knowledge comparisons. Furthermore, we build on this endpoint and propose a GraphQL-based federated endpoint that allows unified access to data from other scholarly infrastructures.…”
Section: Introductionmentioning
confidence: 99%